Note on the distribution of fossil Reptilia of Karroo age - Haughton, S. H. (Bernard Price Institute for Palaeontological Research, 1963)
Reviews briefly the geographical and stratigraphical distribution of reptilia of Karroo age, both within and beyond the confines of the southern hemishpere. Draws attention to the need for further environmental and population studies.
Main article
Keywords: Reptilia; Karoo